Therapeutic effects of non-invasive, individualized, transcranial neuromodulation treatment for voiding dysfunction in multiple sclerosis patients: study protocol for a pilot clinical trial - Tran, Khue (Pilot Feasibility Stud, 2021)
BACKGROUND: Voiding dysfunction (VD) is a common neurogenic lower urinary tract dysfunction (NLUTD) in multiple sclerosis (MS) patients. Currently, the only effective management for VD and urinary retention in MS patients is catheterization, prompting us to look for novel therapeutic options beyond the bladder, such as the brain. Transcranial rotating permanent magnet stimulator (TRPMS) is a non-invasive, portable, multifocal neuromodulator that simultaneously modulates multiple cortical regions, enhancing or attenuating strengths of functional connections between these regions. The objective of this pilot clinical trial is to evaluate the feasibility of a TRPMS trial to address lower urinary tract symptoms in MS patients, through investigating the therapeutic effects of TRPMS in modulating brain regions during voiding initiation and mitigating VD in female MS individuals. METHODS: Ten adult female MS patients with VD (defined as having %post-void residual/bladder capacity (%PVR/BC) ≥ 40% or Liverpool nomogram percentile < 10%) will be recruited for this study. Concurrent urodynamic and functional MRI evaluation with a bladder filling/emptying task repeated three to four times will be performed at baseline and post-treatment. Predetermined regions of interest and their blood-oxygen-level-dependent (BOLD) activation at voiding initiation will be identified on each patient’s baseline anatomical and functional MRI scan, corresponding to the microstimulators placement on their individualized TRPMS treatment cap to either stimulate or inhibit these regions. Patients will receive 10 40-min treatment sessions. Non-instrumented uroflow and validated questionnaires will also be collected at baseline and post-treatment to evaluate clinical improvement. DISCUSSION: Despite the crucial role of the central nervous system in urinary control and its sensitivity to MS, there has been no treatment for urinary dysfunction targeting the brain centers that are involved in proper bladder function. This trial, to our knowledge, will be the first of its kind in humans to consider non-invasive and individualized cortical modulation for treating VD in MS patients. Results from this study will provide a better understanding of the brain control of neurogenic bladders and lay the foundation for a potential alternative therapy for VD in MS patients and other NLUTD in a larger neurogenic population in the future. TRIAL REGISTRATION: This trial is registered at ClinicalTrials.Gov (NCT03574610, 2 July 2018.) and Houston Methodist Research Institute IRB (PRO00019329)